Environmental factors related to the occurrence of oral clefts in a Brazilian subpopulation - Campos Neves, Ana Thereza de Saboia (Niger Med J, 2016)
BACKGROUND: A cross-sectional study was conducted at the Craniofacial Rehabilitation Center in the General Hospital of the University of Cuiabá, Cuiabá city, Mato Grosso, Brazil. MATERIALS AND METHODS: Poisson regression model was used to analyze the relationship between antenatal factors and the occurrence of oral clefts in 116 patients. RESULTS: Oral clefts were more common in males (64.66%) and White race (46.02%). The mean age of the children was 21.91 months. The most common type of cleft was cleft lip and palate (CLP, 55.17%). Maternal and paternal smoking in the first trimester of pregnancy and parity were significantly associated with the occurrence of CLP. Parent's age, educational level, and occupation did not interfere in the occurrence of oral clefts. There was also no significant association between maternal illness, medication use, alcohol consumption, and maternal exposure to chemicals in the first trimester of pregnancy and the occurrence of clefts in this population. CONCLUSION: The analysis of the environmental factors present during the pregnancy of children with oral clefts revealed a significant association between parity (second onward), maternal smoking, and paternal smoking and the occurrence of CL and/or palate in this population.